Innovations in Pediatric Healthcare : Advancements and Future Directions - Rahul Anand; Kiran Dev (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Pediatric healthcare is continuously evolving with advancements in technology and treatment methodologies. This paper examines recent innovations in pediatric care, focusing on digital health tools, telemedicine, and personalized medicine for children. Through literature review and case studies, the paper discusses the impact of these innovations on diagnosis, treatment, and the overall healthcare experience for children. The study emphasizes the need for continuous research and development to improve health outcomes for the pediatric population.